Karakterisasi Mineral dengan Analisis Sayatan Mineragrafi untuk Penentuan Mineralisasi Sphalerite (ZnS) - Kostiawan Sukamto; Mohammad Zaki Mubarok; Ayub Pratama Aris; Ninasafitri Ninasafitri (Universitas Negeri Gorontalo, 2022)
Sphalerite is a mineral rich in Zinc and Iron is the main source of zinc metal production in the world. The purpose of this study was to determine the mineralization in the Cigudeg area, Bogor Regency, West Java, especially the mineralization of Zinc (Zn) by using mineragraphic analysis. Mineragraphic incision analysis is performed to describe the structure and composition of a mineral, the Physico-chemical properties of the mineral, and the presence of associated minerals in the sample. Based on the test results, the mineral component of sphalerite (ZnS) 40-45% as the most dominant component, often contains inclusions of very fine copper grains measuring less than 1 m to 5 m and quartz (SiO2) 10-15% is granular, as for sulfide ore minerals. Others such as chalcopyrite (CuFeS2), pyrite (FeS2), cuprite (Cu2O), and galena (PbS) are present in small amounts.